Effect of periodontal therapy on lactoferrin levels in gingival crevicular fluid. (30th July 2014) - Yadav, N; Lamba, AK; Thakur, A; Faraz, F; Tandon, S; Pahwa, P
Abstract Background The aim of this study was to evaluate lactoferrin quantification as a sensitive and objective method of detecting the degree of periodontal inflammation, oxidative stress and to monitor the effects of periodontal therapy. Methods Fifty subjects were divided into two groups based on gingival index, probing pocket depth, clinical attachment loss and alveolar bone loss: healthy group and periodontitis group with generalized chronic periodontitis. Non‐surgical periodontal therapy was rendered and crevicular fluid samples collected at baseline and four weeks after therapy for lactoferrin quantification using enzyme linked immunosorbent assay. The correlation between clinical parameters and lactoferrin levels was drawn and analysed for both groups. Results The mean level of crevicular lactoferrin in the periodontitis group was 1857.21 ng/ml. The mean level decreased to 1415.03 ng/ml after treatment. The lowest lactoferrin concentration was seen in the healthy group (75.34 ng/ml). All clinical parameters correlated positively with lactoferrin levels. Conclusions The lactoferrin level was higher in the periodontitis group compared to the healthy group, and reduced with periodontal therapy. Higher levels were associated with higher values of clinical parameters, both before and after therapy. The data indicates that Lactoferrin plays an important role in periodontal disease and crevicular lactoferrin quantification can be a marker for detecting periodontal inflammation, oxidative stress and monitoring periodontal therapy.